Quality Sleep Is Associated With Overnight Metabolic Rate in Healthy Older Adults. (2nd June 2016) - Valenti, Giulio; Bonomi, Alberto G.; Westerterp, Klaas R.
Abstract: Background: Increasing age is associated with an increase in overnight metabolic rate. Objective: To determine the relationship between quality sleep, sleep efficiency, and overnight metabolic rate as measured in a respiration chamber in older participants. Methods: The study design was cross sectional. Forty participants, aged 50 to 83 years (17 males, age 63±7 years, body mass index 25.7±2.3kg/m 2 ) spent one night in a respiration chamber to measure sleep stages by polysomnography and overnight metabolic rate (OMR). Data were collected between 23:00 and 07:00. Subsequently basal metabolic rate (BMR) was measured under a ventilated hood. Quality sleep was calculated as time spent in rapid-eye movement (REM) sleep and slow wave sleep divided by total sleep time, and sleep efficiency was calculated as total sleep time divided by the sleep period time. Body movement was measured between 23:00 and 07:00 with an accelerometer on the wrist. Overnight metabolic rate was adjusted for body size by dividing by basal metabolic rate (OMR/BMR). Results: OMR/BMR was positively associated with age ( r = 0.48, p < .001), and quality sleep was negatively associated with age ( r = −0.51, p < .001). The variance of OMR/BMR was significantly explained by quality sleep ( r = −0.58, p < 0.001). Body movement was negatively related to sleep efficiency ( r = -0.38, p<0.01) with no effect on OMR/BMR. When OMR/BMR was adjusted for quality sleep, the effect of age was non significant. Conclusion: Quality sleep is inversely associated with the age-related rise in overnight metabolic rate, suggesting that increased overnight metabolic rate is a biological sign of ageing as a consequence of diminished quality sleep.